Narrativas do negro na tv: o que dizem as crianças? - Agnaldo Afonso de Sousa (2009)
The main goal of this paper is to discuss the reception process lived by children, referencing the presentation of the Black ethnic on TV. The reseach has been developed with 62 children from 9 to 12 years old, coursing the 3rd and 4th grade of a public school in the Grande Belo Horizonte metropolitan zone. Starting from an active relationship between children and TV principle and the existence of an historically Black ethnic defined by its lack and sidelined, it hopes to understand how do children cognize and receive these expressions, which ones are privileged, which are the recognition elements and which mediations are part of this acceptance process. Having with basic theoretical references, we've based on culture scholars like Stuart Hall and Nestor Canclini, on studies that relate media and education like Rosa Maria Bueno Fischer and Renato Ortiz and the works that make an historical analysis of the Black ethnic participation inside the media space, like Joel Zito Araújos work. When making an approach of the TV as a media that produces and reproduces culture through visual and written expressions, these works point to this media vehicle as a primal on identities construction. From a methodological point of view, we´ve choose a qualitative approach with the researchers interventional participation on tender the tasks for reflection. The activities enfold the presentation and discussion of TV programs, form filling and media-related artifacts. It brings as conclusive elements, the averment of while being active receptors, children perceive changes happened on Black ethnic expressions caused by several factors like social movements pressure and by own discovery, by advertisement, by Black ethnic as a consumer group and also explained by the racial prejudice and deficient presence of the Black ethnic on TV. In the group with other expressions (homosexuals, beautys, etc.) the moral issue appears as an exclusionary element and the comic issue as an acceptance factor of the childrens majority, not depending on an ethnic classification. The childrens perception relationship about the Black ethnic takes a complexity, facing to the several mediation processes founded: in an exchange are founded the own constitution, the social imaginative that refers to an inferior place that is still found present, both on childrens mind as on those who produces TV expressions, the religion, an hegemonic beauty representation based on European Caucasian followed and splurged by the media and several experiences which the children are submitted. A great number of speeches that assert the ignorance or identification with the Black ethnic expression (doesn´t know, doesn´t like) also presents an unplace for the Black ethnic which is concurrent with the own historical reality of its expression. The finding of this unplace forces us to the need of keeping moving ahead on a fight for a TV that inserts the difference and has repercussions in a kind of politic action pointed to the transformation. Finally, related to black children self-declared of the research, though the need of more study groups focused in this unique group, we risk saying, based on data, that Black ethnic expression on TV doesnt bring any affirmative action for the development of these children yet.